Study of Parameter Sensitivity of River Bedform Model Due to Delta Formation Phenomena - Agus Indra Jaya (Jurnal Matematika, Statistika dan Komputasi, 2017)
The phenomenon of delta formation in estuarial region is described using the mathematical model of sediment transport on some interval of river region. The model is stated in second order ordinary differential equation of the river depth. As a consequence, the sediment transport could be restricted in a half of river width. The sensitivity of parameter is shown by consider the river bed formation and the level sets of the river depth and its derivative.